Molecular mechanisms responsible for programmed cell death-inducing attributes of terpenes from Mesua ferrea stem bark towards human colorectal carcinoma HCT 116 cells - Asif, Muhammad; Al-Mansoub, Majed Ahmed; Khan, MD Shamsuddin Sultan; Yehya, Ashwaq Hamid Salem; Ezzat, Mohammed Oday; Oon, Chern Ein; Atif, Muhammad; Majid, Aman Shah Abdul; Majid, Amin Malik Shah Abdul (Journal of Applied Biomedicine, 2017)
The current study explored the in vitro anticancer properties of Mesua ferrea stem bark (SB) extract towards human colon carcinoma HCT116 cells. SB was successively extracted with different solvents using soxhlet apparatus. MTT assay was employed to test toxicity against different cancer and normal cell lines. Active extract (n-Hexane) was fractionated by column chromatography (CC) to get the most active fraction (F-3). Series of in vitro assays were employed to characterize cytotoxic nature of F-3. Antioxidant properties of F-3 were assessed using DPPH, ABTS and FRAP assays followed by GC–MS analysis. Intracellular ROS levels were measured by DCFH-DA fluorescent assay. Finally, cell signalling pathways and their downstream proteins targeted by F-3 were studied using 10-cancer pathway and human apoptosis protein profilers and in silico docking studies. n-Hexane extract and its fraction (F-3) showed potent anti-proliferative effect against HCT 116. Programmed cell death (PCD) studies showed that F-3 modulated the expression of multiple proteins in HCT 116. F-3 showed weak antioxidant activity in all the models, while significant increase in ROS was observed in HCT 116. GC–MS analysis revealed that F-3 was majorly comprised of terpenes. Data of pathway profiler and in silico studies revealed that F-3 down-regulated the expression of NF-κB and HIF-1α pathways. Overall these results demonstrate that anticancer effects of M. ferrea stem bark towards human colon carcinoma are mainly due to its terpenes contents.
Keywords: Adaptor Proteins, Signal Transducing; kolorektální nádory; terpeny; Malpighiaceae; Cell Line, Tumor; rostlinné extrakty; techniky in vitro; Cell Death; buněčná smrt; Plant Extracts; buňky NK; adaptorové proteiny signální transdukční; apoptóza; Colorectal Neoplasms; nádorové buněčné linie; Killer Cells, Natural; Terpenes; Apoptosis; In Vitro Techniques